The Autobiography of Charles Darwin - Darwin, Charles, 1809-1882; Darwin, Francis, Sir, 1848-1925 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Autobiography of Charles Darwin" by Charles Darwin is a memoir written in 1876. Originally titled "Recollections of the Development of my Mind and Character," Darwin penned this personal account for his family. The work traces his intellectual journey and character formation. First published in 1887, the initial edition was censored by his son, removing passages about Darwin's critical views on God and Christianity. These omitted sections were restored in 1958, revealing Darwin's complete, unfiltered reflections. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Autobiography_of_Charles_Darwin
Release date is 1999-12-01
Sue Asscher
Keywords: Darwin, Charles, 1809-1882; Darwin, Charles, 1809-1882. On the origin of species; Naturalists -- Great Britain -- Biography